Utilization of risk assessment tools in management of PAH: A PAH provider survey. (8th April 2022) - Sahay, Sandeep; Balasubramanian, Vijay; Memon, Humna; Poms, Abby; Bossone, Eduardo; Highland, Kristine; Kay, Dana; Levine, Deborah J; Mullin, Christopher J; Melendres‐Groves, Lana; Mathai, Stephen C; Soto, Francisco J; et al.
Abstract: Pulmonary arterial hypertension (PAH) is a chronically progressive fatal disease. A goal‐oriented approach to achieve low risk status has been associated with improved survival. A variety of risk stratification tools are available, but use is low. We conducted a survey to assess potential reasons for under‐utilization. We conducted a survey‐based study of global PAH disease specialists with a goal of assessing risk assessment utilization and identifying modifiable barriers to use. The survey was designed by the American College of Chest Physicians' Pulmonary Vascular Diseases (PVD) NetWork. Respondents were global members of the PVD NetWork and Pulmonary Hypertension Association. Survey invitations were sent electronically to all members. Participation was anonymous and no provider or patient level data was collected. Participants from four countries responded with the majority (84%) being from the United States. Our survey found suboptimal use of any risk stratification tool with 71/112 (63%) reporting use. A total of 85% of the respondents had more than 5 years of experience in managing PAH. REVEAL 2.0 and European Society of Cardiology/European Respiratory Society risk tools were the most commonly used. A total of 44 (65%) surveyed felt that use of risk tools led to change in PAH therapies. Only 6 (9%) felt they prompted additional testing or changed the frequency of follow‐up. A total of 5 (7%) reported they prompted goals of care/palliative care discussions and 2 (3%) that they triggered lung transplant referral. The vast majority indicated that incorporation of risk tools into electronic medical records (EMR) would improve utilization. PAH risk assessment tools remain under‐utilized. Most respondents were experienced PAH clinicians. More than one‐third were not routinely using risk tools. Most felt that risk tools led to PAH therapy changes but few reported impacts on other aspects of care. The most commonly identified barriers to use were time constraints and lack of integration with EMR.